Safety and Effectiveness Outcomes From a 14-Country Cohort of Patients With Multi-Drug Resistant Tuberculosis Treated Concomitantly With Bedaquiline, Delamanid, and Other Second-Line Drugs . (4th March 2022) - Huerga, Helena; Khan, Uzma; Bastard, Mathieu; Mitnick, Carole D; Lachenal, Nathalie; Khan, Palwasha Y; Seung, Kwonjune J; Melikyan, Nara; Ahmed, Saman; Rich, Michael L; Varaine, Francis; Osso, Elna; et al.
Abstract: Background: Concomitant use of bedaquiline (Bdq) and delamanid (Dlm) for multi-drug/rifampicin resistant tuberculosis (MDR/RR-TB) has raised concerns about a potentially poor risk-benefit ratio. Yet this combination is an important alternative for patients infected with strains of TB with complex drug resistance profiles or who cannot tolerate other therapies. We assessed safety and treatment outcomes of MDR/RR-TB patients receiving concomitant Bdq and Dlm, along with other second-line anti-TB drugs. Methods: We conducted a multi-centric, prospective observational cohort study across 14 countries among patients receiving concomitant Bdq-Dlm treatment. Patients were recruited between April 2015 and September 2018 and were followed until the end of treatment. All serious adverse events and adverse events of special interest (AESI), leading to a treatment change, or judged significant by a clinician, were systematically monitored and documented. Results: Overall, 472 patients received Bdq and Dlm concomitantly. A large majority also received linezolid (89.6%) and clofazimine (84.5%). Nearly all (90.3%) had extensive disease; most (74.2%) had resistance to fluoroquinolones. The most common AESI were peripheral neuropathy (134, 28.4%) and electrolyte depletion (94, 19.9%). Acute kidney injury and myelosuppression were seen in 40 (8.5%) and 24 (5.1%) of patients, respectively. QT prolongation occurred in 7 patients (1.5%). Overall, 78.0% (358/458) had successful treatment outcomes, 8.9% died, and 7.2% experienced treatment failure. Conclusions: Concomitant use of Bdq and Dlm, along with linezolid and clofazimine, is safe and effective for MDR/RR-TB patients with extensive disease. Using these drugs concomitantly is a good therapeutic option for patients with resistance to many anti-TB drugs. Abstract : Concomitant bedaquiline and delamanid, along with linezolid and clofazimine, was safe and effective in more than 400 patients from 14 countries. Cardiotoxicity was extremely rare, providing reassuring evidence regarding the co-administration of these agents as part of all-oral multi-drug/rifampicin resistant tuberculosis regimens.